The TCM Preparation Feilike Mixture for the Treatment of Pneumonia: Network Analysis, Pharmacological Assessment and Silico Simulation - Peng, Juqin; Chen, Xiaoxiao; Hou, Min; Yang, Kuo; Yang, Bing; Wang, Pan; Du, Yang; Yu, Qingyuan; Ren, Junguo; Liu, Jianxun (Frontiers in Pharmacology, 2022)
The Feilike mixture (FLKM) is a valid prescription that is frequently used to assist in the clinical treatment of pneumonia. However, the mechanisms of its effects remain unclear. First, through literature evaluation, it was preliminarily determined that FLKM improved clinical symptoms, regulated immune inflammation response and ameliorated pulmonary function. Then, via database search and literature mining, 759 targets of the 104 active compounds of FLKM were identified. The component-target (CT) network showed that the key active compositions were resveratrol, stigmasterol, beta-sitosterol, sesamin and quercetin. 115 targets overlapped with pneumonia-related targets. The PPI network showed that the top six targets were TNF, AKT1, IL6, JUN, VEGFA and MAPK3. KEGG analyses found that the six hub targets were mainly enriched in immune related pathway. Next, in vitro experiment, we observed that FLKM ameliorated pathological injury of lung tissue and reduced neutrophil infiltration in rats with LPS-induced pneumonia. And FLKM decreased the concentration of TNF-α and IL-6 in BALF and downregulated the expression of p38MAPK, AKT and VEGFA in lung tissue. Finally, molecular docking further found that six target proteins all had relatively good binding affinity with the key active compositions of FLKM (all ≤ -5 kcal/mol). Molecular dynamics simulation was employed to assess stability and flexibility of receptor-ligand. Among them, AKT1- stigmasterol bound more stably, and their binding free energies were -47.91± 1.62 kcal/mol. This study reveals core compositions and targets by which FLKM may act to treat pneumonia and provides integrated pharmacological evidence to support its clinical efficacy.